A content analysis of the views of genetics professionals on race, ancestry, and genetics. Issue 4 (2nd October 2018) - Nelson, Sarah C.; Yu, Joon-Ho; Wagner, Jennifer K.; Harrell, Tanya M.; Royal, Charmaine D.; Bamshad, Michael J.
Abstract: Over the past decade, the proliferation of genetic studies on human health and disease has reinvigorated debates about the appropriate role of race and ancestry in research and clinical care. Here we report on the responses of genetics professionals to a survey about their views on race, genetics, and ancestry across the domains of science, medicine, and society. Through a qualitative content analysis of free-text comments from 515 survey respondents, we identified key themes pertaining to multiple meanings of race, the use of race as a proxy for genetic ancestry, and the relevance of race and ancestry to health. Our findings suggest that for many genetics professionals the questions of what race is and what race means remain both professionally and personally contentious. Looking ahead as genomics is translated into the practice of precision medicine and as learning health care systems offer continued improvements in care through integrated research, we argue for nuanced considerations of both race and genetic ancestry across research and care settings.